Coastal habitat conservation : new perspectives and sustainable development of biodiversity in the anthropocene - Espinosa, Free (Elsevier, Academic Press, an Imprint of Elsevier, 2023)
"Coastal Habitat Conservation: New Perspectives and Sustainable Development of Biodiversity in the Anthropocene offers the latest research and approaches to biodiversity conservation in coastal areas. The book synthesizes the background of foundational conservation views and provides new perspectives and recent strategies within a sustainable development context for coastal species and organic life. Written by a team of international authors with expertise in wide-ranging issues of biodiversity conservation, this book analyzes the challenges of conserving marine habitats and species that humanity faces in the Anthropocene era. Sections explore emerging and unforeseen impacts within a changing world, specifically, the marine-based conservation in the context of global change, coastal urbanization and mitigation of its environmental impacts, marine bioinvasions, conservation strategies for of out-of-sight communities like caves, habitat restoration, and the citizen science and its challenging role in monitoring conservation." --Publisher's description.